Edukasi Kenali Tubuhmu: Pendekatan Interaktif Melalui Tarian Dan Media Visual Untuk Pencegahan Kekerasan Seksual Di SDN 060831 - Nayla Syahputri; Dealita Khairani Daulay; Fatwa Abdinan Lubis; Adelia Manurung; Rinaldo Simangunsong; Rambu Mbaja Oru; Trialex Sumardin Lase; Muktar Kahewa Lowi (STIKES Columbia Asia Medan, 2026)
Understanding private body parts is a fundamental aspect of early childhood education to prevent sexual violence, cases of which are increasingly rising. The lack of children's knowledge regarding body privacy and self-protection serves as a primary risk factor. This community service aims to enhance the knowledge of students at SDN 060831 regarding the identification of private body parts and self-protection mechanisms. The implementation method included a preparation phase, participatory education using visual media and dance, and evaluation through pre-tests and post-tests. The results showed a significant increase in students' understanding, as evidenced by the rise in the average knowledge score from 64% during the pre-test to 95% during the post-test. This indicates that interactive educational methods through dance and visuals are effective in instilling an understanding of self-protection in elementary school students.